EFFICIENCY AND ACCURACY ANALYSIS OF THE BLACK BUNCH CENSUS ESTIMATION MODEL ON THE REALIZATION OF FRESH OIL FRUIT BUNCH PRODUCTION - Siti Rakhmi Afriani; Abbi Maulana; Junainah; Stenia Ruski Yusticia; M. Rezky Galang; Bagas Saputra (Universitas Veteran Bangun Nusantara, 2026)
The Black Bunch Census (BBC) method is one of the most widely applied techniques in oil palm plantations for estimating fresh fruit bunch (FFB) production, serving as a basis for harvest planning, labor management, and production target setting. Despite its extensive use in plantation operations, the accuracy of this method requires continuous evaluation to ensure its reliability in reflecting actual field production. This study aimed to assess the accuracy of the Black Bunch Census model by comparing estimated and realized FFB production of Costarica and Sriwijaya 1 oil palm varieties during the period from May to August. The data consisted of estimated and actual values of bunch number and FFB tonnage collected from six plantation blocks. A paired sample t-test was employed to determine the statistical differences between estimated and realized production, while the Mean Absolute Percentage Error (MAPE) was used to evaluate estimation accuracy. The results showed that the estimated number of bunches differed significantly from the realized number of bunches (p < 0.05), with a MAPE value of 76.14%, indicating a high level of prediction error. In contrast, no significant difference was observed between estimated and realized FFB tonnage (p > 0.05), with a MAPE value of 25.12%, suggesting a moderate level of estimation accuracy. Variety-based analysis revealed that Sriwijaya 1 exhibited higher estimation accuracy with a MAPE of 14.73%, whereas Costarica showed a MAPE of 35.52%. Differences in estimation accuracy were likely influenced by fruit census procedures, varietal characteristics, agronomic conditions, environmental factors, and harvesting operations. Keywords: Black Bunch Census, Production estimation, Production realization, Oil palm,Fresh fruit bunch,